Hubungan Terpaan Iklan Mie Sedaap Di Televisi Dan Citra Merek Dengan Minat Beli Produk Mie Sedaap - Nurul Avita Sari; Tandiyo Pradekso (Interaksi Online, 2021)
One of the companies that are willing to pay a lot of money for advertisements on television is Mie Sedaap. Mie Sedaap is one of the instant noodle producers in Indonesia who dares to spend hundreds of billions of billions of advertisements and is able to build its brand with a good brand image to attract consumers to make purchases. But in fact this has not been able to make it the first position as a market leader in the instant noodle business, even in the market share data from 2016 to 2018 shows that the Mie Sedaap brand has decreased. The purpose of this study was to find out whether there is a relationship between Sedaap Mie ad exposure and brand image with the interest in buying delicious noodle products. This research uses explanatory research type (explanation). The population of this study were the people of Semarang, male and female and range 12-60 years old, and had seen Mie Sedaap commercials on television. The sample taken in this study were 60 respondents. This study uses data collection tools and techniques by distributing questionnaires. The data analysis technique used was Kendall tau correlation. The results showed that advertisement exposure and Mie Sedaap brand image had a positive relationship with consumer buying interest. The suggestion given is that Mie Sedaap should be able to increase the frequency of its advertisements at premiere hours such as 18.00-19.00 and increase its brand position by using a packaging design that seems more premium